Multiculturalism within a bilingual framework : language, race, and belonging in Canada - Haque, Eve (University of Toronto Press, 2012)
"From the time of its inception in Canada, multiculturalism has generated varied reactions, none more starkly than between French and English Canadians. In this groundbreaking new work, Eve Haque examines the Government of Canada's attempt to forge a national policy of unity based on 'multiculturalism within a bilingual framework, ' a formulation that emerged out of the Royal Commission on Bilingualism and Biculturalism (1963-70). Uncovering how the policies of bilingualism and multiculturalism are inextricably linked, Haque investigates the ways in which they operate together as part of our contemporary national narrative to favour the language and culture of Canada's two 'founding nations' at the expense of other groups. Haque uses previously overlooked archival material, including transcripts of royal commission hearings, memos, and reports, to reveal the conflicts underlying the emergence of this ostensibly seamless policy. By integrating two important areas of scholarly concern -- the evolution and articulation of language rights in Canada, and the history of multiculturalism in the country -- Haque provides powerful insight into ongoing asymmetries between Canada's various cultural and linguistic groups."--Publisher's website.